Information Management and Market Engineering. Vol. II - Dreier, Thomas Krämer, Jan Studer, Rudi Weinhardt, Christof [Hrsg.] (Studies on eOrganisation and Market Engineering, 2010)
The research program Information Management and Market Engineering focuses on the analysis and the design of electronic markets. Taking a holistic view of the conceptualization and realization of solutions, the research integrates the disciplines business administration, economics, computer science, and law. Topics of interest range from the implementation, quality assurance, and advancement of electronic markets to their integration into business processes and legal frameworks.